DEVELOPMENT OF RADIAL INTERACTION RULES FOR CORROSION IN X42 API 5L PIPELINES - IDRIS, NURUL NEESA (2020)
Pipelines are the most efficient mean used in the oil and gas industry for transporting hydrocarbons. Pipeline failure during its service life due to corrosion defects may induce catastrophic failure and gives impact to many parties. Thus, this research focuses on burst test experiments by using pipeline specimens of type API 5L X42 carbon steel pipeline with nominal outer diameter 4.5 inch with 6 mm wall thickness, under seven radial interacting defects arrangements. The seven radial interacting defect arrangements are described by Colonies 1, 2, 3, 4, 5, 6 and 7. Note that, term colony in this research means multiple corrosions defects interacting together.